Comprehensive Guided Inquiry Learning Model through Digital Concepts for Aquaculture Students: A Review - Megahati S, Ruth Rize Paas; Yuliana, Liza (RADINKA JAYA UTAMA PUBLISHER, 2025)
The abstract nature of the topics is easily understood while learning chemistry through guided inquiry. This article employs the A Review (SLR) technique to review eleven papers released between 2018 and 2023 that deal with teaching chemistry using various guided inquiry models. Three online article databases—ERIC, Scopus, and Google Scholar—were used to retrieve articles methodically. The information in this review will be helpful to educators and researchers who work in chemical education in understanding guided inquiry models, how they impact chemical learning outcomes, and how to apply them to improve students' comprehension of chemistry. The review's conclusions show how various guided inquiry strategies immerse students in a problem, offer them an investigation to work through and provide guidance on how to solve the problem. Guided inquiry models influence chemistry learning outcomes by enhancing metacognition, concept understanding, critical thinking skills, science process skills, learning outcomes, creative thinking abilities, and reducing misconceptions. Many learning models or strategies, including guided inquiry, guided inquiry-based on blended learning, guided inquiry-based on the flipped classroom, guided inquiry model integrated with STEM, and guided inquiry and task hierarchy analysis model in cooperative learning strategy, have also used different chemistry learning models.